Promoting male involvement to improve PMTCT uptake and reduce antenatal HIV infection: a cluster randomized controlled trial protocol - Weiss Stephen M; Jones Deborah; Peltzer Karl; Shikwane Elisa (BMC, 2011)
Abstract Background Despite the availability of a dual therapy treatment protocol and infant feeding guidelines designed to prevent mother to child transmission (PMTCT) of HIV, of the over 1 million babies born in South Africa each year, only 70% of those born to HIV positive mothers receive dual therapy. Similar to other resource-poor nations facing the integration of PMTCT into routine pregnancy and infant care, efforts in South Africa to scale up PMTCT and reduce transmission to < 5% have fallen far short of the United Nation's goal of 50% reductions in paediatric HIV by 80% coverage of mothers. Methods/Design This study proposes to evaluate the impact of combining two evidence-based interventions: a couple's risk reduction intervention with an evidence based medication adherence intervention to enhance male participation in combination with improving medication and PMTCT adherence in antenatal clinics to increase PMTCT overall reach and effectiveness. The study will use a group-randomized design, recruiting 240 couples from 12 clinics. Clinics will be randomly assigned to experimental and control conditions and effectiveness of the combined intervention to enhance PMTCT as well as reduce antenatal seroconversion by both individuals and clinics will be examined. Discussion Shared intervention elements may decrease sexual risk and enhance PMTCT uptake, e.g., increased male participation, enhanced communication, HIV counselling and testing, adherence, serostatus disclosure, suggest that a combined sexual risk reduction and adherence intervention plus PMTCT can increase male participation, increase couples' communication and encourage adherence to the PMTCT process. The findings will impact public health and will enable the health ministry to formulate policy related to male involvement in PMTCT, which will result in PMTCT. Trial registration PACTR201109000318329